The effects of relaxation breathing on fatigue in patients with chronic kidney disease undergoing hemodialysis - Sutinah Sutinah; Rasyidah Azhari (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2020)
Background: Fatigue is one of the common complaints in patients with chronic kidney disease undergoing hemodialysis. It would affect the quality of life of clients with a prevalence of 92.2%. The conditions has no more attention and consider as normal, and sustainable for a long time, patient would be suffered the psychological problems. The health workers must care about that matter to prevent further complications. How to reduce or manage a fatigue to patients is recommended to do breathing exercises as non-pharmacological care.Purpose: Knowing the effects of relaxation breathing on fatigue in patients with chronic kidney disease undergoing hemodialysisMethods: The type of research used is quantitative quasi experimental, non equivalent, control group pre test and post test design. The population in this study were all patients with chronic kidney disease undergoing hemodialysis and with the sample of 76 respondents. Samples were taken using purposive sampling technique.Results: The average levels a fatigue score before (50.18) and after having a breathing relaxation techniques was (46.45) with p value = 0.043 (<0.05). It can be concluded that deep breathing relaxation techniques has effects on the reduction in a fatigue in patients with chronic kidney disease undergoing hemodialysis at Raden Mattaher Jambi hospital.Conclusion: Deep breathing relaxation techniques can reduce reduction in a fatigue in patients with chronic kidney disease undergoing hemodialysis at Raden Mattaher Jambi hospital. Recommendation to hospital management to be applied a deep breathing relaxation techniques as standard of operational procedures (SOP) in the context of nursing care, especially to patients with chronic kidney disease undergoing hemodialysis in hemodialysis ward.